2015
DOI: 10.1111/nph.13615
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression ofTaRSL4gene by genome interplay shapes root hair length in allopolyploid wheat

Abstract: SummaryPolyploidy is a major driving force in plant evolution and speciation. Phenotypic changes often arise with the formation, natural selection and domestication of polyploid plants. However, little is known about the consequence of hybridization and polyploidization on root hair development.Here, we report that root hair length of synthetic and natural allopolyploid wheats is significantly longer than those of their diploid progenitors, whereas no difference is observed between allohexaploid and allotetrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 70 publications
4
53
0
Order By: Relevance
“…Of note, RSL4 is rapidly degraded after root hair elongation is initiated; Pi deficiency significantly increases the synthesis and half-life of RSL4 (Datta et al, 2015). The function of RSL4 appears to be conserved; natural and synthetic allopolyploid wheat form longer root hairs than their diploid progenitors, a trait that was positively correlated with the expression level of TaRSL4 (Han et al, 2016). This result is in line with the findings of Stetter et al (2015), who observed longer and denser root hairs in polyploid Arabidopsis accessions.…”
Section: The Control Of Root Hair Elongation and Lengthsupporting
confidence: 82%
See 1 more Smart Citation
“…Of note, RSL4 is rapidly degraded after root hair elongation is initiated; Pi deficiency significantly increases the synthesis and half-life of RSL4 (Datta et al, 2015). The function of RSL4 appears to be conserved; natural and synthetic allopolyploid wheat form longer root hairs than their diploid progenitors, a trait that was positively correlated with the expression level of TaRSL4 (Han et al, 2016). This result is in line with the findings of Stetter et al (2015), who observed longer and denser root hairs in polyploid Arabidopsis accessions.…”
Section: The Control Of Root Hair Elongation and Lengthsupporting
confidence: 82%
“…This result is in line with the findings of Stetter et al (2015), who observed longer and denser root hairs in polyploid Arabidopsis accessions. Consistent with a crucial function of root hairs particularly in nutrient-poor environments, overexpression of TaRSL4 led to increased shoot fresh biomass under such conditions (Han et al, 2016).…”
Section: The Control Of Root Hair Elongation and Lengthmentioning
confidence: 61%
“…As early as 1979, significant differences for seminal root numbers of 7‐day‐old plants were reported among Triticum species with different ploidy levels (Sivasithamparam et al ., ). Until recently, we found that synthetic and natural allopolyploid wheats have significantly longer root hairs than those of their diploid progenitors (Han et al ., ). Here, we reported that the average LRNPR in the natural and synthetic allohexaploid wheats was significantly higher than that of allotetraploid wheat.…”
Section: Discussionmentioning
confidence: 97%
“…There are three class I genes in Brachypodium , BdRSL1 , BdRSL2 or BdRSL3 , and ectopic expression of any of these genes in Brachypodium increases root hair length and density (Kim & Dolan, ). Increasing the expression of related RSL genes in rice, Arabidopsis and wheat also increased root hair length (Han et al ., ; Kim & Dolan, ; Kim et al ., ). The present study used transgenic Brachypodium differing in root hair length to test the hypothesis that longer root hairs improve P nutrition in P‐deficient soil.…”
Section: Introductionmentioning
confidence: 99%